(untitled) (Journal of economic and management development research, 2026)
Empowering teacher development through digitalization is a crucial driver in building an education powerhouse. Relevant policy documents from the Ministry of Education have outlined strategic plans to promote the digital transformation of the teaching workforce via artificial intelligence technology. However, in practice, teacher digital literacy training faces structural misalignment between "supply-oriented" and "demand-oriented" approaches. From the perspective of complex systems theory in economics, this study examines the paradox of "resource abundance and capability deficiency" coexisting in current digital transformation efforts for teacher development. It identifies the root cause as oversimplifying teacher development as a technical training issue while neglecting the cognitive construction, contextual embedding, and value alignment dimensions of teachers as complex adaptive agents. The research proposes shifting from "resource provision" to "ecological construction," advocating for a new paradigm of teacher development through "human-machine collaboration," refining precise profiling and dynamic assessment of teacher digital literacy, and establishing an empowering governance mechanism for teacher development. This fundamental transformation in teacher development models aims to provide theoretical support and practical pathways for cultivating high-quality teaching professionals in the AI era.